The Accommodation and Care System for Unaccompanied Minors in Austria - Saskia Heilemann (Social Work & Society, 2017)
In the context of the unprecedented number of migrants and refugees crossing the Mediterranean for Europe in 2015, Austria experienced a significant increase in the number of unaccompanied minors (UAM) applying for asylum. The article outlines the organizational and legislative changes that were introduced with regard to the accommodation and care of asylum-seeking UAM. Some became necessary in order to alleviate pressure from the reception system, others in order to transpose EU directives into national law. Thereby, the article provides the reader with information regarding the reception system for UAM in Austria, and the living situation of UAM. Drawing from legislative texts, policy documents, research reports, journal articles, media and press releases, internet sources, and statistical data, it becomes clear that the information available is sufficient to understand the Austrian reception system for UAM, but not to assess their living situation. In order to evaluate the accommodation and care provisions and to understand the integration potential and challenges that UAM are presented with, further statistics and primary research are needed. This, in turn, requires more data and a better linking of databases.